PEMBUATAN AKTA IKRAR WAKAF DI KECAMATAN RASAU JAYA (TINJAUAN REGULATIF DAN IMPLEMENTATIF) - Waskur Waskur (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The regulation of waqf in Indonesia has shown very good development, following the enactment of Law No. 41 of 2004 concerning Waqf. However, problems arise in the implementation phase. This is shown by the number of waqf lands that have not registered the Waqf Pledge Deed to the Waqf Pledge Deed Maker Official (PPAIW) at the Office of Religious Affairs. Based on observations made by researchers in Rasau Jaya District, it is known that there are still many mosques whose land has not been registered with the Office of Religious Affairs. By using the juridical-empirical research method, the author questions more about the arrangement of the waqf pledge deed in Indonesia, as well as its implementation at the author's research locus, namely the Rasau Jaya sub-district. The conclusion that the problem arises is due to several reasons, including: unclear registration information, unsystematic flow and time of manufacture, lack of public awareness of the importance of the Waqf Pledge Deed, and the lack of socialization of waqf law carried out by the KUA of Rasau Jaya District.